Physico-Chemical Characterization and Dietary Fiber of Mango (Mangífera Indica L.) Grown in Northeast of Brazil - Padilha, Maria R. F.; Guerra, Nonete B.; Andrade, Samara A. C.; Shinohara, Neide K. S.; Machado, José (Revista Geama, 2018)
Numerous studies show that eating fruits has been inversely linked with chronic disease, type hypertension and significant reduction in the risk of cardiovascular events. And this balanced natural combination of bioactive compounds present in fruits and vegetables cannot be mimicked by industrialized food. Therefore, it is important to encourage the consumption of natural foods, but for this we must know your existing content in foods. Three mangoes cultivars (Mangifera indica L.) were evaluated for physico-chemical characterization and dietary fiber during their development (unripe and ripe) and after post-harvest treatments. The results are in agreement with the evolution of the analyzed parameters between the development stages studied and show that regardless the post-harvest treatment, the fruits didn’t lose the ability to ripe. At the ripe stage, the highest total dietary fiber was presented by Espada and Tommy Atkins cvs. From these data, at quantitative level, mangoes can be considered a good source of dietary fiber, thus potentially beneficial to human health.